Memaknai Sistem Pengendalian Manajemen, Kepemimpinan Dan Ideologi Gender Pemimpin Pada Salah Satu UMKM Minangkabau - Ulil Azmi; Sany Dwita; Mayar Afriyenti (Universitas Negeri Padang, 2019)
This study discusses the meaning of the management control system, leadership and gender ideology of leaders in one of the Minangkabau UMKM. The purpose of this study was to reveal how the implementation of the management control system was influenced by the culture and gender ideology of Minangkabau female leaders. This research is a qualitative research with an interpretative paradigm using the lens of anthropology from an emic and ethic perspective. Emic views come from the results of interviewing the interpretations of the research subjects while the ethic views come from the theories, literature and interpretations of outsiders. The analysis of emic and ethic views gets a deep understanding in this research. The difference between this research and previous research is that this study discusses more about the feminine potential of female leaders in implementing MCS, then this research was conducted on one of the Minangkabau UMKM. This study found that female leaders in the implementation of MCS will use their feminine potential in leadership, namely loving, loving, gentle and well-spoken words. Female leaders will use the family concept in leading so that they can be accepted and listened to by their employees. So gender leadership will produce gender MCS based on the nature of compassion and help. the recommendation for further research is to be able to examine the influence of the concept of Islam in the implementation of MCS